A high mass transfer and low pressure drop porous cloth sealing plate collaborative spray flue gas desulfurization process
Patent Information
- Application Number
- CN202611386222.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-30
AI Technical Summary
然而,普通聚酯多孔布的表面润湿性有限,浆液容易收缩为不连续液珠,布面纤维及纤维交叉区域不能被充分利用
1、经受控表面水解和亲水复合层处理后,聚酯多孔布表面形成较多极性基团及微细凹凸结构,喷淋浆液到达布面后能够沿纤维和纤维交叉点迅速铺展,不易收缩为相互分离的大液珠。双层多孔布采用间隔、旋转和错位设置,烟气通过下层布孔后被分割为多股气流,再经过上层布孔进行二次分割;气流在两层布之间不断改变流动路径,并对布面液膜产生剪切,使液膜持续变薄、破裂和重新形成。由此增加了实际参与二氧化硫吸收的气液接触面积,缩短了二氧化硫在液膜中的扩散距离,同时提高了液膜表面的更新频率,因而无需单纯依靠增加浆液循环量即可改善气液传质条件。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of flue gas treatment technology, belonging to patent classification number B01D53 / 50, specifically a high mass transfer, low pressure drop porous cloth sealing plate synergistic spray flue gas desulfurization process. Background Technology
[0002] Limestone-gypsum wet flue gas desulfurization primarily absorbs sulfur dioxide from flue gas through a spray slurry. Sulfur-containing flue gas flows upwards from the bottom of the absorption tower, while limestone slurry is sprayed downwards from the spray layer, creating a counter-current contact. After entering the slurry, the sulfur dioxide is neutralized by the limestone and converted into gypsum dihydrate under the action of oxidizing air. This process utilizes widely available and relatively low-cost raw materials, making it suitable for treating large-flow industrial flue gas.
[0003] During the spraying process, gas-liquid mass transfer mainly occurs on the surface of the slurry droplets. Due to the influence of the flue gas inlet configuration, tower wall effect, and spray coverage, localized gas velocity differences easily appear across the absorber cross-section. In areas with higher gas velocities, the flue gas passage time is shorter, while in areas with lower gas velocities, the slurry utilization rate is insufficient, resulting in some sprayed liquid failing to form an effective gas-liquid contact interface. Simply increasing the slurry circulation rate can increase the number of droplets, but this increases the energy consumption of the circulation pump and cannot fundamentally improve the flue gas distribution and liquid film renewal state.
[0004] By installing a perimeter-sealed porous fabric sealing plate between the spray layers, flue gas can pass through the plate surface along a predetermined channel, allowing the descending slurry to form a liquid film on the porous fabric surface. As the flue gas passes through the fabric pores, it cuts and agitates the liquid film, thereby increasing the gas-liquid contact area. However, the surface wettability of ordinary polyester porous fabric is limited, and the slurry easily shrinks into discontinuous droplets, preventing full utilization of the fabric fibers and fiber cross-sections. While using smaller pores or increasing the liquid holding capacity of the plate surface is beneficial for forming a continuous liquid film, it increases capillary opening pressure, liquid layer static pressure, and two-phase flow resistance.
[0005] To reduce drag, the porosity of the porous support plate can be increased, and the vents can be designed with smooth inlets and gradually expanding outlets. However, with increased porosity, the unsupported distance of the porous fabric across the vents increases. The hydrophilically treated porous fabric holds more slurry during continuous spraying, and its wet load causes the fabric layer to deflect downwards into the vents. When the deflected portion enters the gradually expanding outlet of the channel, it reduces the effective ventilation cross-section, causing the local flue gas velocity to rise again and weakening the original drag-reducing effect of the streamlined channels. Therefore, there is a mutual constraint between the hydrophilic liquid-holding capacity of the mass transfer interface and the cross-sectional stability of the low-pressure-drop channels.
[0006] The technical problem to be solved by this invention is how to improve the spreading ability of porous cloth to spray slurry, increase the effective mass transfer area of the cloth surface, reduce the additional pressure drop of the porous cloth sealing plate, and suppress the cross-hole deflection caused by the hydrophilic cloth layer due to wet liquid retention, so that the porous cloth sealing plate can maintain a stable gas-liquid mass transfer interface and effective air passage section under continuous spraying conditions. Summary of the Invention
[0007] The purpose of this invention is to provide a high mass transfer, low pressure drop porous cloth sealing plate synergistic spray flue gas desulfurization process to solve the technical problems mentioned in the background art.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A high-mass-transfer, low-pressure-drop porous fabric-sealed plate synergistic spray flue gas desulfurization process includes the following steps: Surface hydrolysis of polyester porous fabric is performed to form a water-resistant and hydrophilic composite layer containing polyvinyl alcohol and silica particles on the surface of the hydrolyzed polyester porous fabric, resulting in at least two layers of modified porous fabric. A porous support plate with at least two regions of different local porosity is prepared, and a streamlined vent is formed on the porous support plate, which includes a smooth inlet section, a short throat section and a gradually expanding outlet section in sequence along the flue gas flow direction; An alkali-resistant inorganic fiber load-bearing mesh and a pre-vulcanized elastomer support strip are set between the porous support plate and the modified porous cloth. At least two layers of modified porous cloth are spaced apart and installed in a staggered manner in the plate surface direction to seal the periphery of the porous support plate, thereby obtaining a porous cloth sealing plate. The porous cloth sealing plate is installed between the lower spray layer and the upper spray layer of the desulfurization absorption tower, so that the flue gas containing sulfur dioxide passes through the lower spray layer, the porous cloth sealing plate and the upper spray layer in sequence, and the limestone slurry forms a liquid film on the surface of the modified porous cloth. The slurry after absorbing sulfur dioxide is returned to the slurry pool for air oxidation.
[0009] Preferably, the surface hydrolysis includes: arranging the polyester porous material in an aqueous sodium hydroxide solution with a concentration of 8-12 g / L, treating it at 60-65°C for 25-35 min, with a bath ratio of 1:15-1:20; After hydrolysis, the product is sequentially washed with water, neutralized with a citric acid aqueous solution with a mass fraction of 0.3% to 0.5%, and washed with water until the pH is 6.5 to 7.5. The drying weight loss of the polyester porous fabric is 0.5% to 1.5%, and the tensile strength retention rate is not less than 95%.
[0010] Preferably, the water-resistant hydrophilic composite layer is formed using a two-bath method, comprising: The surface-hydrolyzed polyester porous fabric is impregnated in a coating bath containing 2.0%–2.5% PVA-1799, 1.0%–1.2% silica sol with a particle size of 12–20 nm (based on SiO2), and 0.5%–0.8% silica sol with a particle size of 70–100 nm (based on SiO2). The pH of the coating bath is 7.5–9.0, the wet pick-up rate of the impregnation is 60%–70%, and the fabric is pre-dried at 75–85°C for 3–5 min after impregnation. The pre-dried porous polyester fabric is sprayed or coated onto a matching roller using a post-crosslinking bath containing glyoxal and phosphoric acid. The effective component of glyoxal in the post-crosslinking bath is 0.35% to 0.60%, the pH is 2.8 to 3.3, the amount of glyoxal used is 8% to 10% of the dry weight gain of polyvinyl alcohol, the contact time of the coating is 20 to 60 seconds, then pre-dried at 75 to 85°C for 2 to 4 minutes, and cured at 115 to 125°C for 4 to 6 minutes. After curing, it is washed with water until neutral and then dried.
[0011] Preferably, the polyester porous fabric is a PET monofilament mesh fabric with a single layer mesh size of 3.0–5.0 mm, a monofilament diameter of 0.5–0.8 mm, and a geometric porosity of not less than 70%. The spacing between two adjacent layers of modified porous fabric is 8–12 mm, and the two layers of modified porous fabric are rotated relative to each other in the plate direction by 30°–45° and staggered by 0.4–0.6 mesh pitches. The distance between the modified porous fabric near the porous support plate and the gradually expanding outlet section is 3–5 mm.
[0012] Preferably, the porous support plate is a modular polypropylene support plate with a thickness of 8-12 mm; according to the flue gas pressure distribution upstream of the installation section of the porous support plate, the plate surface is divided into a high-pressure zone, a medium-pressure zone, and a low-pressure zone, and the local opening rates of the high-pressure zone, the medium-pressure zone, and the low-pressure zone are 34%-38%, 41%-45%, and 48%-52%, respectively, and the average opening rate of the porous support plate is 40%-46%.
[0013] Preferably, the streamlined vent is a racetrack-shaped vent with a minor axis of 25–32 mm, a major axis of 45–60 mm, and a ratio of major axis to minor axis of 1.6–2.2; the radius of the rounded inlet section is 0.15–0.25 times the hydraulic diameter of the vent; the length of the short throat section is 0.15–0.25 times the thickness of the porous support plate; and the diffusion half-angle of the gradually expanding outlet section is 5°–7°. The liquid-facing surface of the porous support plate is also provided with a drainage groove communicating with the streamlined vent, the drainage groove being 2–3 mm deep and 4–6 mm wide.
[0014] Preferably, the alkali-resistant inorganic fiber load-bearing mesh is a high-zirconium alkali-resistant glass fiber mesh with a ZrO2 content of not less than 16%, and its mesh size is 4-6 mm and its areal density is 100-160 g / m³. 2The opening ratio is not less than 78%, and the installation pretension is 0.3-0.6 kN / m; the pre-vulcanized elastomer support strip is an EPDM rubber strip with a thickness of 1.0-1.8 mm, a width of 3-5 mm, and a Shore A hardness of 55-65. The EPDM rubber strip is only set along the solid ribs of the porous support plate, and its projected coverage is not higher than 8% of the area of the porous support plate; the porous support plate, EPDM rubber strip, high zirconium alkali-resistant glass fiber mesh and modified porous cloth are stacked in sequence and fixed by mechanical means.
[0015] Preferably, the sulfur dioxide-containing flue gas is cooled to 45–60°C by the lower spray layer and then passes upward through a porous cloth sealing plate. The limestone slurry sprayed from the upper spray layer passes sequentially through two layers of modified porous cloth and a porous support plate before returning to the slurry pool. The empty tower flue gas velocity in the absorption section is 1.8–3.5 m / s, and the liquid-to-gas ratio is 8–12 L / Nm³. 3 The pH of the circulating slurry is 5.2 to 5.8.
[0016] Preferably, the limestone slurry has a solid content of 8% to 15%, a CaCO3 content of not less than 90% in the limestone, a limestone particle size d90 of not more than 58 μm, and a Ca / S molar ratio of 1.00 to 1.03. The effective circulation retention time in the slurry tank is not less than 4.2 minutes, and the amount of oxidizing air is 1.5 to 2.5 times the theoretical oxygen demand, so that the absorbed sulfites are oxidized and form gypsum dihydrate.
[0017] Compared with the prior art, the beneficial effects of the present invention are: 1. After controlled surface hydrolysis and hydrophilic composite layer treatment, the surface of the polyester porous fabric forms numerous polar groups and a fine, uneven structure. Upon reaching the fabric surface, the sprayed slurry can rapidly spread along the fibers and fiber intersections, preventing it from shrinking into large, separated droplets. The double-layer porous fabric employs a spaced, rotated, and staggered arrangement. Flue gas, after passing through the lower layer's pores, is divided into multiple airflow streams, which are then further divided by the upper layer's pores. The airflow continuously changes its flow path between the two layers, shearing the liquid film on the fabric surface, causing the liquid film to continuously thin, break, and reform. This increases the actual gas-liquid contact area involved in sulfur dioxide absorption, shortens the diffusion distance of sulfur dioxide in the liquid film, and increases the renewal frequency of the liquid film surface. Therefore, it is not necessary to simply increase the slurry circulation volume to improve gas-liquid mass transfer conditions.
[0018] 2. The porous support plate features differentiated porosity based on the flue gas pressure distribution in different areas of the plate surface. This allows for greater flow resistance in high-pressure areas and a larger ventilation area in low-pressure areas, thereby suppressing the concentration of flue gas in localized regions. The ventilation holes employ a smooth inlet, short throat, and small-angle gradually expanding outlet structure, which reduces the constriction caused by sudden flue gas contraction and the backflow and energy loss caused by sudden expansion. The liquid drainage grooves on the plate surface also guide locally accumulated slurry to adjacent ventilation holes, preventing the formation of liquid layers with significant thickness differences. The above structure primarily reduces the orifice shape resistance, local high-speed resistance, and additional resistance caused by non-uniform liquid accumulation in the porous support plate, resulting in a more uniform distribution of flue gas on the plate surface. It also controls the wet pressure drop of the porous sealing plate while maintaining mass transfer of the liquid film on the fabric surface.
[0019] 3. As the hydrophilic porous fabric improves its ability to spread and retain slurry, the wet weight of the fabric layer also increases accordingly. However, the streamlined vent holes have large orifice sizes, and the portion of the fabric layer crossing the orifice lacks continuous rigid support, making it prone to deflecting downwards into the gradually expanding outlet under the influence of slurry weight and flue gas pressure fluctuations. Once the fabric layer enters the gradually expanding outlet, the original flow channel cross-section shrinks, and the local flue gas velocity and resistance increase accordingly, making it impossible to stably maintain the pressure reduction effect of the streamlined channels. To address this issue, a high-zirconium alkali-resistant glass fiber mesh and a pre-vulcanized EPDM rubber strip are jointly installed between the porous support plate and the modified polyester porous fabric. The high-zirconium alkali-resistant glass fiber mesh has a high tensile modulus and a small elongation under stress. When tensioned, it can cross the vent holes to bear the wet weight of the fabric layer and distribute the load originally concentrated above a single orifice along the warp and weft directions to the solid ribs of the adjacent support plate. The high zirconium content allows the glass fiber mesh to maintain its load-bearing performance well in calcium-containing slurry and acid-base fluctuation environments. The pre-vulcanized EPDM rubber strip is laid only on the solid ribs of the support plate. Under pressure, it forms a continuous elastic fulcrum, uniformly transferring the load from the fiberglass mesh to the rigid support plate. Simultaneously, it maintains the tension of the fiberglass mesh through elastic recovery and compensates for local displacements caused by module assembly deviations, temperature changes, and flue gas pressure fluctuations. If only fiberglass mesh is used, uneven line contact easily forms between the rigid mesh and the solid ribs of the support plate, making it difficult to maintain balanced pretension over a long period. If only EPDM rubber strip is used, its own stiffness is insufficient to bear the wet weight of the fabric across large vent holes. The combination of the two allows the EPDM rubber strip to provide elastic support, pre-tension retention, and load buffering, while the high-zirconium alkali-resistant fiberglass mesh provides cross-hole bearing and in-plane load diffusion, ensuring the fabric maintains a contour close to the design plane under continuous spraying. Because the fiberglass mesh has a high opening ratio, and the EPDM rubber strip is only located in the solid rib area of the support plate, this combination suppresses wet deflection without significantly occupying the vent cross-section, thus resolving the constraint between hydrophilic liquid retention reinforcement and low-pressure drop channel stability. Detailed Implementation
[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Example 1 A high-mass-transfer, low-pressure-drop porous fabric-sealed plate synergistic spray flue gas desulfurization process includes the following steps: Take two sheets, each with an area of 0.90m². 2 Surface density is 300 g / m³ 2 The PET monofilament mesh has a mesh size of 3.0mm, a monofilament diameter of 0.5mm, and a geometric opening rate of 73.5%, with a total dry weight of 0.54kg.
[0022] Dissolve 64.8g of sodium hydroxide in water and bring the volume to 8.10L to prepare an 8g / L sodium hydroxide aqueous solution. Add the above-mentioned PET monofilament mesh at a bath ratio of 1:15 and treat at 60℃ for 25min. Prepare a 6.00kg 0.3% citric acid aqueous solution by taking 18g of citric acid and 5.982kg of water. Neutralize the washed mesh in this solution for 2min, and then wash with water until the pH of the rinsing solution reaches 6.5. The criteria for proceeding to the next process are a drying weight loss of not less than 0.5% and not more than 1.5% and a tensile strength retention rate of not less than 95%.
[0023] Take 0.205 kg of PVA-1799 and 9.295 kg of deionized water, stir at 90℃ for 45 min, and cool to below 40℃; then add 0.333 kg of silica sol with a solid content of 30% and a particle size of 15 nm and 0.167 kg of silica sol with a solid content of 30% and a particle size of 80 nm in sequence, and mix to obtain 10.00 kg of coating bath A. The PVA-1799 content in bath A is 2.05%, and the contents of the two silica sols (calculated as SiO2) are 1.0% and 0.5%, respectively. The pH of bath A is 7.5. Impregnate the mesh fabric with bath A, control the wet pick-up rate at 60%, and then pre-dry at 75℃ for 3 min.
[0024] Take 43.75g of a 40% glyoxal aqueous solution, 2.00g of a 10% phosphoric acid aqueous solution, and 4.954kg of deionized water, and mix them to prepare a 5.00kg crosslinking bath (B bath). The effective glyoxal content in bath B is 0.35%, and the pH is 2.8. Spray bath B onto the pre-dried mesh fabric, controlling the wet pickup rate at 35%. After contact for 20 seconds, immediately pre-dry at 75℃ for 2 minutes, and then cure at 115℃ for 4 minutes. The cured mesh fabric is washed with water until neutral and dried at 80℃.
[0025] A porous support plate was fabricated using polypropylene modules with a thickness of 8 mm. Based on the flue gas pressure distribution in front of the plate, the plate surface was divided into an equivalent high-pressure zone, a medium-pressure zone, and a low-pressure zone. The local porosity of the three zones was 34%, 41%, and 48%, respectively, with an average porosity of 41%. The vents were racetrack-shaped holes with a short axis of 25 mm and a long axis of 45 mm. The radius of the gas inlet fillet was 0.15 times the hydraulic diameter of the vent, the short throat length was 1.2 mm, and the diffusion half-angle of the gradually expanding outlet was 5°. A 2 mm deep and 4 mm wide drainage channel, connected to the adjacent vents, was provided on the liquid-facing surface of the support plate.
[0026] A 6.5m thick, 1.0mm wide, 3mm wide, Shore A hardness 55 pre-vulcanized EPDM rubber strip with a diameter of 0.90m² is laid on the solid ribs of the support plate; a sheet of EPDM rubber with a diameter of 0.90m² is then installed on the EPDM rubber strip. 2 The ZrO2 content is 16%, the mesh size is 4mm, and the areal density is 100g / m³. 2 A high-zirconium alkali-resistant fiberglass mesh with an opening ratio of 78% is used, with an installation pretension of 0.30 kN / m. The projected coverage of the EPDM rubber strip is less than 8%. Two layers of modified PET mesh are installed above the fiberglass mesh. The lower layer is 3 mm away from the channel outlet, and the two layers are 8 mm apart. The upper layer is rotated 30° relative to the lower layer and staggered by 0.4 mesh pitches. Each layer is mechanically fixed using perimeter frames and node clips.
[0027] A porous cloth sealing plate is installed inside an absorption tower with an inner diameter of 1.00m. A lower spray layer is set 0.60m below the plate, and an upper spray layer is set 0.80m above it. 240kg of limestone powder with a CaCO3 content of 90% and a d90 of 58μm and 2760kg of process water are used to prepare 3000kg of limestone slurry with a solid content of 8% under continuous stirring. A flow rate of 4370Nm³ is introduced into the absorption tower. 3 The flue gas contains SO2 and has an inlet temperature of 100℃. After being cooled to 45℃ by the lower spray layer, the flue gas passes through the porous cloth sealing plate at an empty tower velocity of 1.8 m / s. The total slurry circulation volume is 35.0 m³ / h. 3 / h, of which 14.0m 3 / h fed into the lower spray layer, 21.0m 3 The liquid-to-gas ratio is 8.0 L / Nm³, which is fed into the upper spray layer at a rate of / h. 3 The operating pH was maintained at 5.2 by adding limestone slurry, and the Ca / S molar ratio was controlled at 1.00. The effective volume of the slurry tank was 2.50 m³. 3 The circulation residence time is 4.29 min; the amount of oxidation air is controlled at 1.5 times the theoretical oxygen demand.
[0028] Example 2 A high-mass-transfer, low-pressure-drop porous fabric-sealed plate synergistic spray flue gas desulfurization process includes the following steps: Take two sheets, each with an area of 1.30m². 2 Surface density is 300 g / m³ 2 The PET monofilament mesh has a mesh size of 4.0mm, a monofilament diameter of 0.65mm, and a geometric opening rate of 74.0%, with a total dry weight of 0.78kg.
[0029] Dissolve 136.5g of sodium hydroxide in water and bring the volume to 13.65L to prepare a 10g / L sodium hydroxide aqueous solution. Add this solution to the PET monofilament mesh at a bath ratio of 1:17.5 and treat at 62.5℃ for 30min. Prepare an 8.00kg (w / w) citric acid aqueous solution using 32g of citric acid and 7.968kg of water. Neutralize the washed mesh with this solution for 2min, then wash again until the pH of the rinsing solution reaches 7.0. Control the drying weight loss of the mesh to be 0.5%–1.5% and the tensile strength retention rate to be no less than 95%.
[0030] Take 0.450 kg of PVA-1799 and 18.384 kg of deionized water, stir at 92℃ for 50 min, and then cool to 38℃. Add 0.733 kg of silica sol with a solid content of 30% and a particle size of 15 nm and 0.433 kg of silica sol with a solid content of 30% and a particle size of 80 nm sequentially to obtain 20.00 kg of coating bath A. The PVA-1799 content in bath A is 2.25%, and the contents of the two silica sols (calculated as SiO2) are 1.1% and 0.65%, respectively. The pH of bath A is 8.2. The mesh fabric is impregnated with bath A, with a wet pick-up rate of 65%, and then pre-dried at 80℃ for 4 min.
[0031] Take 118.75 g of 40% glyoxal aqueous solution, 1.20 g of 10% phosphoric acid aqueous solution, and 9.880 kg of deionized water, and mix them to prepare a 10.00 kg crosslinking bath (B bath). The effective glyoxal content in bath B is 0.475%, and the pH is 3.05. Spray bath B onto the pre-dried mesh fabric with a wet pickup rate of 30%. After contact for 40 seconds, pre-dry at 80℃ for 3 minutes, and then cure at 120℃ for 5 minutes. The cured mesh fabric is washed with water until neutral and dried at 80℃.
[0032] A porous support plate was fabricated using polypropylene modules with a thickness of 10 mm. The local porosity in the high-pressure, medium-pressure, and low-pressure zones was 36%, 43%, and 50%, respectively. The three zones were arranged with equivalent area, resulting in an average porosity of 43%. The racetrack-shaped vent has a minor axis of 28 mm and a major axis of 52 mm. The gas inlet fillet radius is 0.20 times the hydraulic diameter of the vent, the short throat length is 2.0 mm, and the diffusion half-angle of the gradually expanding outlet is 6°. A drainage groove with a depth of 2.5 mm and a width of 5 mm is provided on the liquid-facing surface of the support plate.
[0033] A 9.0m thick, 1.4mm wide, 4mm wide, Shore A hardness 60 pre-vulcanized EPDM rubber strip with a diameter of 1.30m² is laid on the solid ribs of the support plate; a sheet of EPDM rubber with a diameter of 1.30m² is then installed on top of the strip. 2 The ZrO2 content is 16.5%, the mesh size is 5mm, and the areal density is 130g / m³. 2 A high-zirconium alkali-resistant fiberglass mesh with an opening ratio of 81% is used, with an installation pretension of 0.45 kN / m. Two layers of modified PET mesh are installed above the fiberglass mesh. The lower mesh is 4 mm away from the channel outlet, and the two layers are 10 mm apart. The upper mesh is rotated 37.5° relative to the lower mesh and staggered by 0.5 mesh pitches. Each layer is fixed by mechanical clamping.
[0034] A porous cloth sealing plate was installed inside an absorption tower with an inner diameter of 1.20m. 920kg of limestone powder with a CaCO3 content of 92% and a d90 of 45μm, and 7080kg of process water were used to prepare 8000kg of limestone slurry with a solid content of 11.5%. A flow rate of 8900 Nm³ was introduced into the absorption tower. 3 The flue gas contains SO2 and has an inlet temperature of 110℃. After being cooled to 52℃ by the lower spray layer, the flue gas passes through the porous cloth sealing plate at an empty tower velocity of 2.6 m / s. The total slurry circulation volume is 89.0 m³ / h. 3 / h, of which 35.6m 3 / h fed into the lower spray layer, 53.4m 3 The liquid-to-gas ratio is 10.0 L / Nm³, which is fed into the upper spray layer at a rate of / h. 3 The operating pH was maintained at 5.5, and the Ca / S molar ratio was controlled at 1.015. The effective volume of the slurry tank was 8.0 m³. 3 The circulation residence time was 5.39 min; the amount of oxidation air was controlled at 2.0 times the theoretical oxygen demand.
[0035] Example 3 A high-mass-transfer, low-pressure-drop porous fabric-sealed plate synergistic spray flue gas desulfurization process includes the following steps: Take two sheets, each with an area of 1.70m². 2 Surface density is 300 g / m³ 2 The PET monofilament mesh has a mesh size of 5.0mm, a monofilament diameter of 0.8mm, and a geometric opening rate of 74.3%, with a total dry weight of 1.02kg.
[0036] Dissolve 244.8g of sodium hydroxide in water and bring the volume to 20.40L to prepare a 12g / L sodium hydroxide aqueous solution. Add this solution to the PET monofilament mesh at a bath ratio of 1:20 and treat at 65℃ for 35 minutes. Prepare a 10.00kg (w / w) citric acid aqueous solution by mixing 50g of citric acid with 9.950kg of water. Neutralize the washed mesh with this solution for 3 minutes, then wash until the pH of the rinsing solution reaches 7.5. Control the drying weight loss of the mesh to be no more than 1.5% and the tensile strength retention rate to be no less than 95%.
[0037] Take 0.625 kg of PVA-1799 and 22.708 kg of deionized water, stir at 95℃ for 60 min, and then cool to 35℃. Add 1.000 kg of silica sol with a solid content of 30% and a particle size of 20 nm, and 0.667 kg of silica sol with a solid content of 30% and a particle size of 100 nm, respectively, to obtain 25.00 kg of coating bath A. The PVA-1799 content in bath A is 2.5%, and the contents of the two silica sols (based on SiO2) are 1.2% and 0.8%, respectively. The pH of bath A is 9.0. The mesh fabric is impregnated with bath A, with a wet pick-up rate of 70%, and then pre-dried at 85℃ for 5 min.
[0038] Take 150.0 g of 40% glyoxal aqueous solution, 0.40 g of 10% phosphoric acid aqueous solution, and 9.850 kg of deionized water, and mix them to prepare a 10.00 kg crosslinking bath (B bath). The effective glyoxal content in bath B is 0.60%, and the pH is 3.3. Spray bath B onto the pre-dried mesh fabric with a wet pickup rate of 25%. After contact for 60 seconds, pre-dry at 85℃ for 4 minutes, and then cure at 125℃ for 6 minutes. The cured mesh fabric is washed with water until neutral and dried at 80℃.
[0039] A porous support plate was fabricated using 12mm thick polypropylene modules. The local porosity of the high-pressure, medium-pressure, and low-pressure zones was 38%, 45%, and 52%, respectively. The three zones were arranged with equivalent area, resulting in an average porosity of 45%. The high-pressure and medium-pressure zones used racetrack-shaped vents with a short axis of 32mm and a long axis of 60mm, while some low-pressure zones used racetrack-shaped vents with a short axis of 27.5mm, a long axis of 60mm, and a length-to-short axis ratio of 2.18. The local porosity was adjusted by increasing the number of vents. The gas inlet radius was 0.25 times the hydraulic diameter of the vent, the short throat length was 3.0mm, and the diffusion half-angle of the gradually expanding outlet was 7°. A 3mm deep and 6mm wide drainage channel was provided on the liquid-facing surface of the support plate.
[0040] A 12.0m thick, 1.8mm wide, Shore A hardness 65 pre-vulcanized EPDM rubber strip with a diameter of 1.70m² is laid on the solid ribs of the support plate; a sheet of EPDM rubber with a diameter of 1.8mm is then installed on top of the strip. 2 The ZrO2 content is 17%, the mesh size is 6mm, and the areal density is 160g / m³.2 A high-zirconium alkali-resistant fiberglass mesh with an opening ratio of 84% is used, with an installation pretension of 0.60 kN / m. Two layers of modified PET mesh are installed above the fiberglass mesh. The lower layer is 5 mm away from the channel outlet, and the two layers are 12 mm apart. The upper layer is rotated 45° relative to the lower layer and staggered by 0.6 mesh pitches. Each layer is fixed using a perimeter frame and node clips.
[0041] A porous cloth sealing plate was installed inside an absorption tower with an inner diameter of 1.40 m. 2250 kg of limestone powder with a CaCO3 content of 95% and a d90 of 35 μm and 12750 kg of process water were used to prepare 15000 kg of limestone slurry with a solid content of 15%. A flow rate of 15900 Nm³ was introduced into the absorption tower. 3 The flue gas contains SO2 and has an inlet temperature of 125℃. After being cooled to 60℃ by the lower spray layer, the flue gas passes through the porous cloth sealing plate at an empty tower velocity of 3.5 m / s. The total slurry circulation volume is 190.8 m³ / h. 3 / h, of which 76.3m 3 / h fed into the lower spray layer, 114.5m 3 The liquid-to-gas ratio is 12.0 L / Nm³, which is fed into the upper spray layer at a rate of / h. 3 The operating pH was maintained at 5.8, and the Ca / S molar ratio was controlled at 1.03. The effective volume of the slurry tank was 15.0 m³. 3 The circulation residence time is 4.72 min; the amount of oxidation air is controlled at 2.5 times the theoretical oxygen demand.
[0042] Comparative Example 1: Compared with Example 1, the PET monofilament mesh was not subjected to sodium hydroxide surface hydrolysis, PVA-dual particle size silica sol coating, and glyoxal post-crosslinking treatment. The same unmodified PET monofilament mesh of the same specifications was used directly, and the other materials, structures, and operating conditions were the same as in Example 1.
[0043] Comparative Example 2: Compared with Example 1, only one layer of modified PET monofilament fabric treated in the same way was set up, without the use of double-layer spacing, rotation and misalignment structure, and the other materials, structures and operating conditions were the same as in Example 1.
[0044] Comparative Example 3: Compared with Example 1, the porous support plate does not divide into high-pressure, medium-pressure and low-pressure zones. The local opening rate of the entire plate surface is uniformly set to 41%. The remaining materials, channel structure and operating conditions are the same as in Example 1.
[0045] Comparative Example 4: Compared with Example 1, the porous support plate uses a straight runway hole with a short axis of 25 mm, a long axis of 45 mm and an average opening rate of 41%. It does not have a smooth inlet section, a short throat section, a gradually expanding outlet section and a drainage trough. The other materials, structures and operating conditions are the same as those in Example 1.
[0046] Comparative Example 5: Compared with Example 1, no high zirconium alkali-resistant glass fiber mesh and pre-vulcanized EPDM rubber strip were set between the porous support plate and the modified PET monofilament mesh. The modified PET monofilament mesh was directly fixed to the porous support plate by the peripheral pressure frame. The other materials, structures and operating conditions were the same as in Example 1.
[0047] Comparative Example 6: Compared with Example 1, only the same high zirconium alkali-resistant glass fiber mesh of the same specification was set between the porous support plate and the modified PET monofilament mesh, and the pre-vulcanized EPDM rubber strip was not set. The other materials, structures and operating conditions were the same as those in Example 1.
[0048] Comparative Example 7: Compared with Example 1, only the same pre-vulcanized EPDM rubber strips of the same specifications were set on the solid ribs of the porous support plate, and the high zirconium alkali-resistant glass fiber mesh was not set. The other materials, structures and operating conditions were the same as those in Example 1.
[0049] Performance testing 1. Water droplet diffusion time. This was determined according to GB / T 21655.1—2023, "Evaluation of the moisture absorption and quick-drying properties of textiles—Part 1: Single-item combination test method". Three 100mm × 100mm samples were cut from the liquid contact side of each sample and conditioned to moisture equilibrium in the standard atmosphere specified in GB / T 6529. The samples were flattened and fixed without pre-stretching. One drop (approximately 0.05mL) of grade III water conforming to GB / T 6682 was placed on the center of the sample using a dropper, with the dropper tip no more than 10mm from the sample surface and at a 45° angle. The timing started at the point of contact with the sample and ended when the specular reflection of the droplet completely disappeared, recording the time to 0.1s. The arithmetic mean of the measurements from the three samples was taken as the water droplet diffusion time.
[0050] 2. SO2 removal efficiency and total number of gas-phase mass transfer units. Examples 1-3 were operated according to their respective described tower diameter, flue gas volume, empty tower gas velocity, liquid-to-gas ratio, slurry solid content, pH, and Ca / S; Comparative Examples 1-7 were operated under the gas-liquid conditions of Example 1, with only the corresponding structure or treatment steps changed. The inlet SO2 mass concentration was controlled at 2000 mg / m³. 3 (Standard conditions, dry basis) After each sample was continuously run for 60 minutes to reach steady state, samples were simultaneously taken at the tower inlet and outlet according to the monitoring requirements of HJ / T 397—2007. Two instruments conforming to HJ 629—2026 "Determination of Sulfur Dioxide in Waste Gas from Stationary Sources - Portable Non-dispersive Infrared Absorption Method" were used to determine the SO2 concentration. The sampling tubes were heated throughout the process and equipped with a two-stage particulate filter. Zero-point gas and certified SO2 standard gas were used for verification before and after the test. The instruments recorded data continuously for 30 minutes at 1-minute intervals. Flue gas temperature, moisture content, pressure, and standard dry flow rate were determined according to GB / T 16157—1996. SO2 removal efficiency was calculated as η=[Cin Q in -C out Q out ] / (C in Q in The calculation is based on ) × 100%, where C is the standard dry basis SO2 mass concentration and Q is the standard dry flue gas flow rate; the total number of gas phase mass transfer units is calculated according to N0G = ln(y in / y out The formula is calculated, where y is the standard dry basis SO2 mole fraction. Each sample was subjected to three independent steady-state tests, and the arithmetic mean was taken.
[0051] 3. Wet Pressure Drop of the Porous Cloth Sealing Plate Assembly. Following the static pressure measurement principles of GB / T 16157—1996, four circumferentially distributed static pressure holes were installed at 0.5D points upstream and downstream of the porous cloth sealing plate assembly, where D is the inner diameter of the tower body. The four static pressure holes at the same cross-section were connected to an equalizing ring, which in turn was connected to a differential pressure transmitter with a range of 0–2 kPa and an accuracy class of 0.25. Each sample was continuously run under the gas-liquid conditions of the SO2 removal performance test for 60 minutes. Differential pressure data were collected for 600 seconds at a frequency of 1 Hz. Non-steady-state data caused by spray start-up and shutdown were discarded, and the resulting arithmetic mean was used as the wet pressure drop of the assembly. Each sample was measured independently three times, and the arithmetic mean was taken.
[0052] 4. Outlet section gas velocity variation coefficient. A gas velocity measurement section was set at 1.0D above the porous fabric sealing plate assembly. Sixteen measuring points were arranged according to the equal area distribution principle of GB / T 16157—1996. Dynamic pressure at each point was measured using a calibrated S-type Pitot tube and micromanometer. Simultaneously, flue gas temperature, static pressure, and moisture content were measured, and the axial gas velocity at each point was calculated. The probe was held for 30 seconds after moving to each measuring point, and the average value of the stable readings over the following 20 seconds was taken. The cross-sectional gas velocity variation coefficient was calculated as CV=[Σ(v... i -v) 2 / (n-1)] 1 / 2 Calculated as / v×100%, where v i Let v be the gas velocity at the i-th measuring point, v be the average gas velocity at 16 measuring points, and n be 16; each sample is measured independently 3 times and the arithmetic mean is taken.
[0053] 5. Maximum wet deflection after 72 hours. A self-developed wet load-bearing capacity test method was used. With the fabric cover installed and neither aeration nor spraying initiated, 25 measuring points were arranged at the mid-span and quarter-span positions of the fabric layer, using a rigid reference frame fixed to the tower wall as the zero point. The system was then continuously operated for 72 hours according to the corresponding sample's gas velocity, liquid-to-gas ratio, slurry temperature, and solid content. Measurements were taken point-by-point using a laser displacement sensor with a range of 0–10 mm and a resolution of 0.01 mm through a sealed observation window, under continuous gas and liquid flow conditions. Data was continuously collected for 30 seconds at each measuring point, and the median value was taken. The maximum downward displacement of each measuring point relative to the zero point was taken as the maximum wet deflection after 72 hours. Each sample was tested repeatedly using three independent sets of components, and the arithmetic mean was taken.
[0054] Table 1: The SO2 removal efficiencies of Examples 1-3 were 93.8%, 96.5%, and 98.2%, respectively, with the corresponding increase in the total number of gas-phase mass transfer units from 2.78 to 4.02. This indicates that the hydrophilic fabric layer can maintain a continuously spreading and renewed liquid film when the liquid-to-gas ratio, slurry pH, and treatment intensity are increased. Meanwhile, the wet pressure drop of the module increased from 338 Pa to 718 Pa as the empty tower gas velocity increased from 1.8 m / s to 3.5 m / s, indicating that increasing the treatment load leads to a corresponding increase in resistance. This change is consistent with the law that the resistance of the gas-liquid two-phase channel increases with the load. The outlet gas velocity CV of Examples 1-3 was all below 8%, indicating that the partitioned orifice has a stable flow-equalizing effect for different tower diameters and treatment loads.
[0055] Compared to Example 1, the water diffusion time in Comparative Example 1 increased from 1.3 s to 17.6 s, and the SO2 removal efficiency decreased by 4.3 percentage points, indicating that the untreated PET fabric is difficult to form a fully spread reaction liquid film. Its lower pressure drop and deflection are mainly due to reduced liquid holding capacity and do not represent improved mass transfer performance. In Comparative Example 2, the pressure drop decreased to 306 Pa after using a single-layer fabric, but the desulfurization efficiency also decreased to 91.1%, reflecting the mass transfer loss caused by shortening the gas-liquid contact path. In Comparative Example 3, after eliminating the partitioned openings, the outlet gas velocity (CV) increased to 17.3%; in Comparative Example 4, after using straight holes and eliminating the guide drainage structure, the wet pressure drop increased to 446 Pa. These results respectively verify the effects of gradient flow equalization and streamlined channels on controlling gas flow deviation and local resistance.
[0056] With the increased liquid holding capacity of the hydrophilic double-layer fabric, the fabric layer is prone to wet deflection above the large openings and intrusion into the flow passage area, thereby amplifying local resistance and gas velocity unevenness. In Comparative Example 5, after simultaneously removing the high-zirconium alkali-resistant glass fiber mesh and the pre-vulcanized EPDM rubber strip, the maximum wet deflection reached 4.32 mm after 72 hours, and the module pressure drop and outlet gas velocity CV increased to 472 Pa and 18.7%, respectively. The high-zirconium alkali-resistant glass fiber mesh distributes the wet load of the fabric layer to the solid ribs of the sealing plate through cross-hole bearing, while the pre-vulcanized EPDM rubber strip forms a continuous elastic support at the solid ribs, maintaining the clamping pre-tightening force and absorbing the displacement caused by spray pulsation; the rubber strip can also alleviate the stress concentration at the edge of the glass fiber mesh, so that the high modulus bearing capacity of the glass fiber mesh and the elastic restoring of the rubber strip complement each other. When both are set simultaneously, the deflection is 0.72 mm, which is 50.7% lower than that of Comparative Example 6 which only has fiberglass mesh and 73.4% lower than that of Comparative Example 7 which only has EPDM rubber strip. It also reduces pressure drop and air velocity CV at the same time, indicating that the combination can stabilize the wet flow cross section without blocking the effective opening.
[0057] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the essence and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-mass-transfer, low-pressure-drop porous cloth-sealed plate synergistic spray flue gas desulfurization process, characterized in that, Includes the following steps: Surface hydrolysis of polyester porous fabric is performed to form a water-resistant and hydrophilic composite layer containing polyvinyl alcohol and silica particles on the surface of the hydrolyzed polyester porous fabric, resulting in at least two layers of modified porous fabric. A porous support plate with at least two regions of different local porosity is prepared, and a streamlined vent is formed on the porous support plate, which includes a smooth inlet section, a short throat section and a gradually expanding outlet section in sequence along the flue gas flow direction; An alkali-resistant inorganic fiber load-bearing mesh and a pre-vulcanized elastomer support strip are set between the porous support plate and the modified porous cloth. At least two layers of modified porous cloth are spaced apart and installed in a staggered manner in the plate surface direction to seal the periphery of the porous support plate, thereby obtaining a porous cloth sealing plate. The porous cloth sealing plate is installed between the lower spray layer and the upper spray layer of the desulfurization absorption tower, so that the flue gas containing sulfur dioxide passes through the lower spray layer, the porous cloth sealing plate and the upper spray layer in sequence, and the limestone slurry forms a liquid film on the surface of the modified porous cloth. The slurry after absorbing sulfur dioxide is returned to the slurry pool for air oxidation.
2. The flue gas desulfurization process according to claim 1, characterized in that, The surface hydrolysis includes: arranging polyester porous structures in an aqueous sodium hydroxide solution with a concentration of 8-12 g / L, treating at 60-65°C for 25-35 min, with a bath ratio of 1:15-1:20; After hydrolysis, the product is sequentially washed with water, neutralized with a citric acid aqueous solution with a mass fraction of 0.3% to 0.5%, and washed with water until the pH is 6.5 to 7.
5. The drying weight loss of the polyester porous fabric is 0.5% to 1.5%, and the tensile strength retention rate is not less than 95%.
3. The flue gas desulfurization process according to claim 2, characterized in that, The water-resistant and hydrophilic composite layer is formed using a two-bath method, including: The surface-hydrolyzed polyester porous fabric is impregnated in a coating bath containing 2.0%–2.5% PVA-1799, 1.0%–1.2% silica sol with a particle size of 12–20 nm (based on SiO2), and 0.5%–0.8% silica sol with a particle size of 70–100 nm (based on SiO2). The pH of the coating bath is 7.5–9.0, the wet pick-up rate of the impregnation is 60%–70%, and the fabric is pre-dried at 75–85°C for 3–5 min after impregnation. The pre-dried porous polyester fabric is sprayed or coated onto a matching roller using a post-crosslinking bath containing glyoxal and phosphoric acid. The effective component of glyoxal in the post-crosslinking bath is 0.35% to 0.60%, the pH is 2.8 to 3.3, the amount of glyoxal used is 8% to 10% of the dry weight gain of polyvinyl alcohol, the contact time of the coating is 20 to 60 seconds, then pre-dried at 75 to 85°C for 2 to 4 minutes, and cured at 115 to 125°C for 4 to 6 minutes. After curing, it is washed with water until neutral and then dried.
4. The flue gas desulfurization process according to claim 1, characterized in that, The polyester porous fabric is a PET monofilament mesh with a single layer mesh size of 3.0–5.0 mm, a monofilament diameter of 0.5–0.8 mm, and a geometric porosity of not less than 70%. The spacing between two adjacent layers of modified porous fabric is 8–12 mm. The two layers of modified porous fabric are rotated relative to each other in the plate direction by 30°–45° and staggered by 0.4–0.6 mesh pitches. The distance between the modified porous fabric near the porous support plate and the gradually expanding outlet section is 3–5 mm.
5. The flue gas desulfurization process according to claim 1, characterized in that, The porous support plate is a modular polypropylene support plate with a thickness of 8-12 mm. According to the flue gas pressure distribution upstream of the installation section of the porous support plate, the plate surface is divided into a high-pressure zone, a medium-pressure zone, and a low-pressure zone. The local opening rates of the high-pressure zone, the medium-pressure zone, and the low-pressure zone are 34%-38%, 41%-45%, and 48%-52%, respectively, and the average opening rate of the porous support plate is 40%-46%.
6. The flue gas desulfurization process according to claim 5, characterized in that, The streamlined vent is racetrack-shaped, with a minor axis of 25–32 mm and a major axis of 45–60 mm, the ratio of the major axis to the minor axis being 1.6–2.
2. The radius of the rounded inlet section is 0.15–0.25 times the hydraulic diameter of the vent, the length of the short throat section is 0.15–0.25 times the thickness of the porous support plate, and the diffusion half-angle of the gradually expanding outlet section is 5°–7°. The liquid-facing surface of the porous support plate is also provided with a drainage groove communicating with the streamlined vent, the drainage groove being 2–3 mm deep and 4–6 mm wide.
7. The flue gas desulfurization process according to claim 1, characterized in that, The alkali-resistant inorganic fiber load-bearing mesh is a high-zirconium alkali-resistant glass fiber mesh with a ZrO2 content of not less than 16%, and its mesh size is 4-6 mm with an areal density of 100-160 g / m². 2 The opening ratio is not less than 78%, and the installation pretension is 0.3-0.6 kN / m; the pre-vulcanized elastomer support strip is an EPDM rubber strip with a thickness of 1.0-1.8 mm, a width of 3-5 mm, and a Shore A hardness of 55-65. The EPDM rubber strip is only set along the solid ribs of the porous support plate, and its projected coverage is not higher than 8% of the area of the porous support plate; the porous support plate, EPDM rubber strip, high zirconium alkali-resistant glass fiber mesh and modified porous cloth are stacked in sequence and fixed by mechanical means.
8. The flue gas desulfurization process according to claim 1, characterized in that, Sulfur dioxide-containing flue gas is cooled to 45–60°C by the lower spray layer and then passes upward through a porous cloth sealing plate. The limestone slurry sprayed from the upper spray layer passes sequentially through two layers of modified porous cloth and a porous support plate before returning to the slurry pool. The empty tower flue gas velocity in the absorption section is 1.8–3.5 m / s, and the liquid-to-gas ratio is 8–12 L / Nm³. 3 The pH of the circulating slurry is 5.2 to 5.
8.
9. The flue gas desulfurization process according to claim 8, characterized in that, The limestone slurry has a solid content of 8% to 15%, a CaCO3 content of not less than 90% in the limestone, a limestone particle size d90 of not more than 58 μm, and a Ca / S molar ratio of 1.00 to 1.
03. The effective circulation retention time in the slurry tank is not less than 4.2 minutes, and the amount of oxidizing air is 1.5 to 2.5 times the theoretical oxygen demand, so that the absorbed sulfite is oxidized and forms gypsum dihydrate.
